2020
DOI: 10.1016/j.cell.2020.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Microglia Require CD4 T Cells to Complete the Fetal-to-Adult Transition

Abstract: Summary The brain is a site of relative immune privilege. Although CD4 T cells have been reported in the central nervous system, their presence in the healthy brain remains controversial, and their function remains largely unknown. We used a combination of imaging, single cell, and surgical approaches to identify a CD69 + CD4 T cell population in both the mouse and human brain, distinct from circulating CD4 T cells. The brain-resident population was derived through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
190
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 229 publications
(230 citation statements)
references
References 109 publications
(136 reference statements)
6
190
1
2
Order By: Relevance
“…Manual gating of flow cytometry data was done using FlowJo v10 software (Tree Star). tSNE, FlowSOM and heatmap analysis were performed on iLN samples from day 7 post-vaccination using R (version 4.0.2) using code that has previously been described 56 . The antibodies used for surface staining are listed in Key Resources Table .…”
Section: Methodsmentioning
confidence: 99%
“…Manual gating of flow cytometry data was done using FlowJo v10 software (Tree Star). tSNE, FlowSOM and heatmap analysis were performed on iLN samples from day 7 post-vaccination using R (version 4.0.2) using code that has previously been described 56 . The antibodies used for surface staining are listed in Key Resources Table .…”
Section: Methodsmentioning
confidence: 99%
“…Within the first three months of life in humans, its size increases more than 50% from the time of birth, reaching 90% of the size of the adult organ within the first five years of life (72). In this period, neuronal development takes place (73) and it is supported and shaped by maternal microbiota (74)(75)(76)(77)(78)(79).…”
Section: Introductionmentioning
confidence: 99%
“…98,99 In addition, recruited T cells secrete cytokines that modulate the activity of CNS-resident immune cells, such as microglia and astrocytes. [100][101][102] In pioneering studies, Wekerle and coworkers demonstrated that the commensal gut flora controls autoreactive T cells that migrate to the CNS and cause inflammation and tissue pathology. 103 Follow-up studies defined alterations in the gut microbiota associated with MS 104 and identified specific components of the microbiome involved in the regulation of effector and regulatory T cells.…”
Section: Modulation Of Inflammation In the Central Nervous System (Cns)mentioning
confidence: 99%